1984
DOI: 10.1001/jama.1984.03350200046020
|View full text |Cite
|
Sign up to set email alerts
|

Snuff-Induced Hypertension in Pheochromocytoma

Abstract: The dipping of snuff provoked paroxysmal hypertension that induced myocardial ischemia in a 69-year-old woman with pheochromocytoma. The diagnosis of her tumor was delayed by a report of a falsely low urine metanephrine level, resulting from interference with the metanephrine assay by meglumine present in the urine because of contrast coronary angiography performed on the day of urine collection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

1987
1987
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(3 citation statements)
references
References 10 publications
0
2
0
1
Order By: Relevance
“…15 Apart from acute, non-sustained elevation in blood pressure in normal subjects, paroxysms of severe hypertension were described in a patient with phaechromocytoma following snuff dipping. 25 Marked elevations in blood pressure were attributed to an acute surge in catecholamine levels, and these were associated with acute coronary episodes. Nicotine enhances the release of catecholamine and is associated with acute increases in heart rate and blood pressure.…”
Section: Slt Use Cardiovascular Risks and Diabetes Mellitusmentioning
confidence: 99%
“…15 Apart from acute, non-sustained elevation in blood pressure in normal subjects, paroxysms of severe hypertension were described in a patient with phaechromocytoma following snuff dipping. 25 Marked elevations in blood pressure were attributed to an acute surge in catecholamine levels, and these were associated with acute coronary episodes. Nicotine enhances the release of catecholamine and is associated with acute increases in heart rate and blood pressure.…”
Section: Slt Use Cardiovascular Risks and Diabetes Mellitusmentioning
confidence: 99%
“…An acute rise in blood pressure following ST use has also been noted in some case reports emanating from the US. [57][58][59][60] Some authors 14,[60][61][62] have suggested that sodium or liquorice in ST may contribute to the blood pressure increase, though a direct effect of nicotine is more commonly referred to. Two studies, 55,56 in which the controls were given, as a placebo, snuffs that did not contain tobacco and were nicotine-free, observed no acute rise in blood pressure.…”
Section: Blood Pressurementioning
confidence: 99%
“…Hypertension artérielle (HTA) En 1984, Mc Phaul et al [37] ont rapporté un cas d'HTA paroxystique avec ischémie myocardique lors de consommation de snus chez une femme de 69 ans ayant un phéochro-mocytome. La consommation aiguë de snus provoque une augmentation paroxystique de la fréquence cardiaque (FC) et de la pression artérielle (PA) systolique et diastolique [38] ; l'augmentation aiguë de la PA et de la FC est principalement observée chez le sujet n'utilisant pas la nicotine habituellement.…”
Section: Accidents Vasculaires Cérébraux (Avc)unclassified